The new pattern and new madness of social media / Nur Hidayyah Shari Shawarudin - Shari Shawarudin, Nur Hidayyah (Faculty of Information Management, 2015)
What's app, Twitter, Facebook, WeChat is a social media that is very popular nowadays. Various different parties have implemented various functions and the tools used by the media. Among the tools that have been used by the social networks, virtual reality, such as Facebook, creating a virtual contact, like sharing text messages, sounds like sending messages via voice record and audio visual like creating a conference, and etc. This will make it easier for users to identify, strengthen, and connect the relationship and so on. This can attract users to use these cutting-edge applications with racing chase progress. Social media can be emerging as the most important tool in people's lives. Various types of communication have created a very complete with the ability to share information with other users, connecting individuals and communities. No other media has become so popular in such a short period of time as social media. The interpersonal communication is having the important communication tools to attract users.